EMBEDDED LINUX BASED ALBUM BROWSER SYSTEM AT MUSIC STORES - Suryadiputra Liawatimena (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2009)
The goal of this research is the creation of an album browser system at a music store based on embedded Linux. It is expected with this system; it will help the promotion of said music store and make the customers activity at the store simpler and easier. This system uses NFS for networking, database system, ripping software, and GUI development. The research method used are and laboratory experiments to test the system’s hardware using TPC-57 (Touch Panel Computer 5.7